COVID‐19 vaccine failure in chronic lymphocytic leukaemia and monoclonal B‐lymphocytosis; humoural and cellular immunity. (5th January 2022) - Shen, Yandong; Freeman, Jane A.; Holland, Juliette; Solterbeck, Ann; Naidu, Kartik; Soosapilla, Asha; Downe, Paul; Tang, Catherine; Kerridge, Ian; Wallman, Lucinda; Van Bilsen, Nenna; Milogiannakis, Vanessa; et al.
Summary: Chronic lymphocytic leukaemia (CLL) is associated with immunocompromise and high risk of severe COVID‐19 disease and mortality. Monoclonal B‐cell lymphocytosis (MBL) patients also have immune impairment. We evaluated humoural and cellular immune responses in 181 patients with CLL (160) and MBL (21) to correlate failed seroconversion [<50 AU/ml SARS‐CoV‐2 II IgG assay, antibody to spike protein; Abbott Diagnostics)] following each of two vaccine doses with clinical and laboratory parameters. Following first and second doses, 79.2% then 45% of CLL, and 50% then 9.5% of MBL patients respectively remained seronegative. There was significant association between post dose two antibody level with pre‐vaccination reduced IgM ( p  < 0.0001), IgG2 ( p  < 0.035), and IgG3 ( p  < 0.046), and CLL therapy within 12 months ( p  < 0.001) in univariate analysis. By multivariate analysis, reduced IgM ( p  < 0.0002) and active therapy ( p  < 0.0002) retained significance. Anti‐spike protein levels varied widely and were lower in CLL than MBL patients, and both lower than in normal donors. Neutralisation activity showed anti‐spike levels <1000 AU/ml were usually negative for both an early viral clade and the contemporary Delta variant and 72.9% of CLL and 53.3% of MBL failed to reach levels ≥1000 AU/ml. In a representative sample, ~80% had normal T‐cell responses. Failed seroconversion occurred in 36.6% of treatment‐naïve patients, in 78.1% on therapy, and in 85.7% on ibrutinib.